Operando Forming of Lattice Vacancy Defect in Ultrathin Crumpled NiVW‐Layered Metal Hydroxides Nanosheets for Valorization of Biomass. Issue 16 (20th January 2023) - Zhang, Baolong; Yang, Zhaohui; Yan, Chuanyu; Xue, Zhimin; Mu, Tiancheng
Abstract: The 2D layered metal hydroxides (LMHs) have been developed for electrooxidation of 5‐hydroxymethylfurfural (HMF). In this work, an effective strategy is proposed to tailor the electronic structure of active sites at the atomic level, which is by introducing defects into the lattice structure. As an example, a series of ultrathin crumpled ternary NiVW‐LMH electrocatalysts with abundant lattice vacancies (denoted as NiVW v ‐LMH) are prepared in this way. The introduction of tungsten (W) endows the catalyst with a special crumpled structure, which promotes the generation of lattice vacancies and thus exposes more unsaturated Ni activity sites. The NiVW v ‐LMH displays superb performance in the electrooxidation of HMF. The Tafel slope for electrodehydrogenation of Ni 2+ OH bond to Ni(OH)O species is 12.04 mV dec −1 . The current density at 1.43 V versus reversible hydrogen electrode (RHE) toward the oxidation reaction of HMF reaches about 193 mA cm −2, which is better than most of the common electrocatalysts, with an 5.37‐fold improvement compared with Ni(OH)2 electrode. The preparation strategy demonstrates in this work can be useful for developing highly efficient electrocatalysts. Abstract : Based on the cation lattice vacancy effect, ultrathin ternary NiVW‐layered metal Hydroxides with rich unsaturated sites is successfully synthesized, which has a highly efficient and stable catalytic effect on biomass resource, 5‐HMF.